Analysis of Memory Effects in Digital Filters with Overflow Arithmetic - Mani Kant Kumar; Haranath Kar (Institute of Advanced Engineering and Science, 2017)
This paper deals with the problem of undesired memory effects in nonlinear digitalfilters owing to the influence of past excitations on future outputs. The nonlinearities under consideration cover the usual types of overflow arithmetic employed in practice. Based on the Hankel norm performance, a new criterion is proposed to ensure the reduction of undesired memory effects in digital filters with overflow arithmetic. In absence of external input, the nonexistence of overflow oscillations is also confirmed by the proposed criterion. A numerical example together with simulation result showing the effectiveness of the criterion is given.